Environmental Regulations, Green Innovation and Performance: An Analysis of Industrial Sector Companies from Developed Countries and Emerging Countries - Jaluza Maria Lima Silva Borsatto; Camila Bazani; Lara Amui (BBR: Brazilian Business Review)
This study analyzes whether the rigor of environmental regulations encourages industrial companies in developed and emerging countries to invest in Green Innovation (GI), and what is the impact on financial performance. The sample was composed of 159 industrial companies, listed in the Financial Times’ 500 largest companies by market value in 2015. For the analysis, Structural Equation Modeling was used to verify the relationship between the variables. The main results were that the strictness of the countries’ environmental regulations, and the size of the companies had a statistically significant positive impact only on construct GI2, composed of the variables Global Compact and environmental investments. Countries competitiveness did not positively influence companies’ GI efforts, and the degree of internationalization of companies had no significant effect on any of the GI constructs. Furthermore, the efforts of companies in GI do not reflect positively on their financial performance.